2021
DOI: 10.1111/1750-3841.15732
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and antimicrobial efficacy of curcumin loaded solid lipid nanoparticles against foodborne bacteria in hamburger patty

Abstract: The aim of the present study was to design a delivery system of curcumin (CU) loaded solid lipid nanoparticles (CU‐CSLNs) for evaluating the antimicrobial properties in hamburger patty. Solid lipid nanoparticle (SLN) was prepared through a homogenizing technique. A response surface methodology was applied to optimize the CU‐CSLNs to minimize the particle size (PS), polydispersity index (PDI), as well as to maximize the zeta potential to avoid aggregation of particles. The optimized sample revealed a spherical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In another study, Alanchari et al. (2021) examined the antibacterial activity of curcumin‐loaded‐SLN (CU‐SLN) and free form of curcumin against S. aureus and E.coli by agar well diffusion. They reported that the encapsulation of curcumin improves the antibacterial activity of curcumin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Alanchari et al. (2021) examined the antibacterial activity of curcumin‐loaded‐SLN (CU‐SLN) and free form of curcumin against S. aureus and E.coli by agar well diffusion. They reported that the encapsulation of curcumin improves the antibacterial activity of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…The most potent antimicrobial activity of PEO-SLN against L. monocytogenes with the approximately inhibition zones of 21 mm for all strains. E. coli O157:H7 and P. aeruginosa had an almost similar inhibition zone (∼ 19 nm), while the Alanchari et al (2021) examined the antibacterial activity of curcumin-loaded-SLN (CU-SLN) and free form of curcumin against S. aureus and E.coli by agar well diffusion. They reported that the encapsulation of curcumin improves the antibacterial activity of curcumin.…”
Section: In Vitro Antibacterial Assay Of Peo-slnmentioning
confidence: 99%
See 1 more Smart Citation
“…In meat products, SLN loading curcumin was evaluated in the antimicrobial activity assay of hamburger patties inoculated with foodborne pathogens. It was shown that curcumin-based SLN was more effective against Gram-positive than Gram-negative bacteria, stored for 8 days [ 121 ]. However, this optimized effect against Gram-positive species is not a rule, since parameters of different lipid compositions of SLN and the cell wall of microorganisms are primary factors [ 122 ] that modulate the biological activities of NDS.…”
Section: Nanostructured Delivery Systems (Ndss)mentioning
confidence: 99%
“…Mint, fennel, and basil EO in yoghurt were able to inhibit the microbial growth [ 165 ]. Meat and related products are more prone to spoilage due to the high levels of protein, high water activity, and diverse microorganisms [ 121 ]. Pathogenic bacteria in meat are responsible for a significant number of foodborne outbreaks ( Listeria monocytogenes , Salmonella spp., E. coli O157:H, and S. aureus ) and deaths [ 166 ].…”
Section: Nanopackaging and Smart Control Of Food Pathogensmentioning
confidence: 99%